2021
DOI: 10.1249/mss.0000000000002641
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Multi-ingredient Supplement on Resistance Training–induced Adaptations

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
2
5
0
1
Order By: Relevance
“…Our findings demonstrate that the myofiber size of untrained males is modulated in part by the responsivity of nAR content to RET, which extends previous reports of AR influencing baseline CSA 13,24,25 . It is worth noting that our previously published study found no effect of supplement on vastus lateralis CSA, but found an effect on biceps and whole‐body lean mass 30 . Our present findings emphasize the role of nAR content in male RET‐induced adaptation since total AR content was unrelated to hypertrophy.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our findings demonstrate that the myofiber size of untrained males is modulated in part by the responsivity of nAR content to RET, which extends previous reports of AR influencing baseline CSA 13,24,25 . It is worth noting that our previously published study found no effect of supplement on vastus lateralis CSA, but found an effect on biceps and whole‐body lean mass 30 . Our present findings emphasize the role of nAR content in male RET‐induced adaptation since total AR content was unrelated to hypertrophy.…”
Section: Discussionsupporting
confidence: 86%
“…Twenty‐six healthy, young males ( n = 13; 21.8 ± 0.6 years) and females ( n = 13; 22.1 ± 0.6 years) were recruited. All participants were recreationally active and did not participate in any structured exercise for a year prior to enrolling in this trial, which was part of a larger investigation examining the effects of a multi‐ingredient supplement on the resistance training adaptive response 30 . For the purposes of this study, the placebo and supplement groups were combined to understand the acute and chronic exercise‐induced changes on AR biology in males and females.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations